Determinant Analysis of Productive Age Women on Participation Oof Visual Inspection with Acetic Acid (Via) Examination In Palembang (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Background: World Health Organization (WHO) showed two of 10.000 women in Indonesia suffer from cervical cancer and an estimated 26 women die each day because cervical cancer. The low early detection performed by productive women lead to cervical cancer incidence is increasing each years. One of prevention cervical cancer is early detection through examination of visual inspection with Acetic Acid (VIA). This study aimed to determinant analyze on productive women towards participation in the VIA in Palembang.Methods: The research method used cross-sectional design, the sampling technique using proportional accidental sampling consisted of 165 respondents which on the inclusion and exclusion criteria . The data collection was done by using a questionnaire home visit CPC-28 Questionare. The data analysis using chi-square and multiple logistic regression. Results: Results showed the proportion of productive women who participated inspection IVA is only 7.9%. Based on the results obtained by multiple logistic regression analysis found significant relationship between education (p value = 0.037; OR = 0.27) and perceived barriers (p value = 0.015; OR = 13) against participation in the IVA examination in productive women in Palembang. Multivariate analysis showed that the perception of barriers is the dominant factor affecting participation in VIA examination in productive age women in Palembang. It is therefore necessary strategies to overcome perceived barriers by women as socialization.Conclusions: Multiple logistic regression analysis found a significant relationship between education and perceived barriers against participation in the IVA examination in productive age women in Palembang.